International symposium on Mediterranean animal germplasm and future human challenges : A joint EAAP-FAO-Ciheam International Symposium - Boyazoglu, J.; Cappuccio, A.; Matassino, D. (Biology - Book Archive pre-2000, 1997)
This compilation of papers and keynote lectures presented at the International Symposium provide an opportunity to assess the position of Mediterranean germplasm at world level, taking into account the challenges for feed requirements, sustainable development of agriculture and regional socio-economic issues. Research on economic and social valorisation of original germplasm provides a new step towards the conservation of farm animal biodiversity.